2013
DOI: 10.5588/ijtld.12.0368
|View full text |Cite
|
Sign up to set email alerts
|

Free tuberculosis diagnosis and treatment are not enough: patient cost evidence from three continents

Abstract: We observed similar patterns and challenges of TB-related costs for patients across the three countries. We advocate for global, united action for TB patients to be included under social protection schemes and for national TB programmes to improve equitable access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 13 publications
(18 reference statements)
9
104
2
3
Order By: Relevance
“…The comparison group included patients from the same month and from the marginalised/vulnerable populations of the same area as the Axshya SAMVAD patients. Second, similar to Mauch et al and Morishita et al [11,23], we included a nationally representative sample, the reference population for which was limited to the Axshya districts ( n  = 285). The findings are also representative of their respective reference populations with potential contaminated exposures excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison group included patients from the same month and from the marginalised/vulnerable populations of the same area as the Axshya SAMVAD patients. Second, similar to Mauch et al and Morishita et al [11,23], we included a nationally representative sample, the reference population for which was limited to the Axshya districts ( n  = 285). The findings are also representative of their respective reference populations with potential contaminated exposures excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we identified many studies in the recent period that determined catastrophic costs due to TB care (diagnosis and treatment), but did not provide data specifically for diagnosis [11,3336]. A systematic review from Africa (studies from 1990 to 2010) revealed that the pre-diagnostic costs for TB varied between 10.4 and 35% of pre-TB AHI [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often conditionality is attached to receiving the transfer, such as regular attendance of medical appointments. While many developed and developing country governments provide such transfers, the World Food Programme is probably the single biggest global provider, having reached 360,000 TB patients and their household members through its food assistance 4 programmes in over ten countries in 2012. In the top ten countries alone, 91,000 index clients were reached while support was also given to an additional 248,000 household members.…”
mentioning
confidence: 99%
“…Bebanan kewangan dan ekonomi ini dilihat menyukarkan mereka mendapatkan rawatan tuberkulosis dan mengakibatkan pesakit-pesakit ini tidak menghabiskan rawatan (Sagbakken et al 2008;Wynne et al 2014). Kajian analisis kos terbaru yang dijalankan di tiga buah negara iaitu Ghana, Vietnam, dan Republik Dominican turut mengesahkan bahawa rawatan dan diagnosis tuberkulosis percuma adalah tidak mencukupi dibuktikan dengan fakta masih terdapat 27.0% hingga 70.0% daripada pesakit-pesakit dalam kajian tersebut terpaksa berhenti kerja dan mengalami kurang pendapatan sehingga memaksa mereka menjual harta dan meminjam wang akibat daripada penyakit tuberkulosis yang dihidapi (Mauch et al 2013).…”
Section: Perbincanganunclassified